COVID-19 and Its Influence on Prevalence of Dementia and Agitation in Australian Residential Aged Care: A Comparative Study - Yunshu Zhu; Ping Yu; Wanqing Li; Ting Song; Zhenyu Zhang; Mengyang Yin; Hui Chen (Rita) Chang; Lixin (Lee) Song; Chao Deng (Psychiatry International)
Agitation is one of the most common and persistent behavioral and psychological symptoms among persons with dementia (PWD) in residential aged care facilities (RACFs). While most studies have explored the general impact of COVID-19 on the mental health and well-being of aged care residents, there has been limited research on the pandemic’s impact on agitation in dementia within RACFs. This knowledge is crucial to ensuring that RACFs are better equipped to handle future public health emergencies. Therefore, this retrospective cohort study investigates the impact of the pandemic on agitation incidents within 40 Australian RACFs. Using Python, we extracted agitation symptoms from nursing notes and compared the frequency and percentage of symptom occurrence pre-pandemic versus during-pandemic. Chi-square tests examined any significant change in the prevalence of dementia and agitation in dementia between the comparative groups and periods. Dementia prevalence dropped significantly during the second year of the pandemic, with a concurrent increase in early-onset dementia cases. Overall, agitation symptoms decreased by 20.1%, but six symptoms significantly increased: resisting (28.98%), wandering (11.78%), restlessness (3.19%), complaining (10.1%), arguing (2.36%), and outbursts (1.74%). Conversely, pacing decreased by 15.88% and speaking loudly decreased by 10.9%. Over half of the care recipients with dementia experienced agitation symptoms 2–5 times each year, increasing from 50.56% in 2019 to 58.28% in 2021. Despite the co-occurrence of symptoms such as falls, confusion, and weakness, there was no evidence to suggest that these comorbidities were specific to COVID-19; rather, they appeared to be prevalent even before the pandemic. Persons with agitation in dementia had a significantly higher death rate during the COVID-19 pandemic than otherwise.